Precarious Work, Insecure Workers: Employment Relations in Transition - Kalleberg, Arne L. (American Sociological Review, 2009)
The growth of precarious work since the 1970s has emerged as a core contemporary concern within politics, in the media, and among researchers. Uncertain and unpredictable work contrasts with the relative security that characterized the three decades following World War II. Precarious work constitutes a global challenge that has a wide range of consequences cutting across many areas of concern to sociologists. Hence, it is increasingly important to understand the new workplace arrangements that generate precarious work and worker insecurity. A focus on employment relations forms the foundation of theories of the institutions and structures that generate precarious work and the cultural and individual factors that influence people's responses to uncertainty. Sociologists are well-positioned to explain, offer insight, and provide input into public policy about such changes and the state of contemporary employment relations.
Keywords: precarious work; precarity